Toxicology : agriculture and environment. - Singh, Dileep K. (Bentham Science Publishers, 2012)
Pesticide control involves killing pest organisms or otherwise preventing them from destructive behavior. Pesticides are either natural or synthetic and are applied to target pests in a myriad of formulations (EC, WP, SP, FP, G etc.) and application technology systems (sprays, baits, slow-release diffusion, dust, etc.). In recent years, the bacterial genes coding for insecticidal proteins have been incorporated into various crops that dealt with the mortality of the pests feeding on them. Many other eco-friendly methods for insect pest control such as Integrated Pest Management (IPM), use of bi.